FROM ECONOMIC ASSET TO SELF-ACTUALIZATION PROJECT: A HISTORICAL ANALYSIS OF THE SHIFTING SYMBOLIC VALUES ​​OF CHILDREN AND THE EMERGENCE OF THE CHILDFREE OPTION - Fikri, Khirpal; Wahyuni, Syarli (PERSPEKTIF: Journal of Social and Library Science, 2025)
This study aims to analyze the historical transformation of children's value from economic assets to emotional symbols and self-actualization projects in modern society and its relationship to the emergence of the childfree phenomenon. Using a historical qualitative approach through a library study of classical and contemporary literature, this study traces the changes in children's values ​​within social, economic, and cultural contexts. The results show that the shift in children's values ​​occurs in layers: from a productive function in pre-modern times, to a symbol of affection in the modern era, to the center of emotional projects that require great sacrifice in post-industrial society. The ideology of intensive parenting positions children as emotionally "priceless," yet simultaneously becomes a source of psychological and financial pressure for parents. The childfree phenomenon emerges as a rational reaction to this symbolic burden, marking a renegotiation of the meaning of happiness and success in life outside the framework of the traditional family. This study concludes that childfree is not a form of moral decadence, but rather a reflection of a new rationality that emphasizes psychological well-being, gender equality, and individual autonomy. This research makes an important academic contribution to expanding the study of family sociology, gender studies, and social history by demonstrating the link between the evolution of children's values ​​and the childfree phenomenon. By combining historical and sociological perspectives, this research opens up new space for understanding how changes in economic structures, moral ideologies, and modern technologies shape human reproductive choices in the post-industrial era.